2011
DOI: 10.1002/smll.201100111
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Growth via Carburization of Stainless Steel and Application in Energy Storage

Abstract: A modified version of the carburization process, a widely established technique used in the steel industry for case hardening of components, is used for the growth of graphene on stainless steel. Controlled growth of high-quality single- and few-layered graphene on stainless steel (SS) foils through a liquid-phase chemical vapor deposition (CVD) technique is reported. Reversible Li intercalation in these graphene-on-SS structures is demonstrated, where graphene and SS act as electrode and current collector, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Recently new materials such as graphene and its derivatives have been used as electrodes in applications such as supercapacitors and batteries9101112. Of the several issues being addressed for electrochemical energy storage devices, high temperature capabilities for powering sensors in oil drilling industries (downhole temperatures are above 120°C), military and space applications has not yet fully addressed.…”
mentioning
confidence: 99%
“…Recently new materials such as graphene and its derivatives have been used as electrodes in applications such as supercapacitors and batteries9101112. Of the several issues being addressed for electrochemical energy storage devices, high temperature capabilities for powering sensors in oil drilling industries (downhole temperatures are above 120°C), military and space applications has not yet fully addressed.…”
mentioning
confidence: 99%
“…Graphene has also been grown by the CVD method on stainless steel substrates [186,187] . Rapid progress in terms of large area deposition of thin fi lms via transfer onto plastic and glass substrates has been taking place in the past few years [188,189] .…”
Section: Graphenementioning
confidence: 99%
“…Besides, C and Fe prefer to form Fe 3 C, rather than to grow graphene on Fe. Despite this misfit, several researchers [22][23][24] have contributed their efforts to growing graphene on steels. John et al [22] developed a synthesis of graphene on commercially stainless steel foils using direct thermal CVD.…”
Section: Introductionmentioning
confidence: 98%
“…They found that the oxide of Mn and Cr along with MnCr 2 O 4 played a key role in graphene growth. Gullapalli et al [23] modified carburization process to obtain graphene on stainless steel foils. Although these successful attempts are inspiring, they did not further explore the application of graphene grown on Fe or steel.…”
Section: Introductionmentioning
confidence: 99%